2022
DOI: 10.1590/1806-9304202200030009
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hearing screening programs: quality indicators and access to health services

Abstract: Objectives: to verify the quality indicators of neonatal hearing screening programs, identify the most prevalent risk factors for hearing loss and analyze access to the Hearing Health Care Network. Methods: cross-sectional study using secondary data. The population are children born in public maternity hospitals from 2015 to 2019. Data collection was carried out in the database of programs and hearing health service. The absolute and relative frequencies of all variables collected and the median, the interqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…From the results of the present study, it can be well understood that in a developing country like India, the challenges that are faced by audiologists at grassroots levels obstruct the implication of an impeccable newborn hearing screening program with a uniform protocol. Our findings in the study stated by the audiologists match with similar challenges reported by several researchers in literature which addresses the problems that a developing country faces while trying to implement and regulate a screening program such as lack of funding, lack of awareness, lack of manpower, low support of inter-disciplinary teams, poor data management systems resulting in loss of follow-up data which are in accordance to the major challenges that an audiologist face [11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…From the results of the present study, it can be well understood that in a developing country like India, the challenges that are faced by audiologists at grassroots levels obstruct the implication of an impeccable newborn hearing screening program with a uniform protocol. Our findings in the study stated by the audiologists match with similar challenges reported by several researchers in literature which addresses the problems that a developing country faces while trying to implement and regulate a screening program such as lack of funding, lack of awareness, lack of manpower, low support of inter-disciplinary teams, poor data management systems resulting in loss of follow-up data which are in accordance to the major challenges that an audiologist face [11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…In Brazil, over the past 5 years, a steady increase in the number of cases of syphilis in pregnant women, congenital syphilis, and acquired syphilis has been observed ( 9 ). This increase is reflected in NHSP programs that present congenital syphilis as one of the most prevalent RIHLs in neonates ( 17 – 19 ). Another factor contributing to congenital syphilis being the most prevalent among congenital infections may be due to the public policy in Brazil that, since 2005 ( 20 ), has made notification of syphilis compulsory in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…As triagens neonatais são uma forma de ação preventiva para identificação de possíveis patologias, para bebês assintomáticos, por meio de testes, com o objetivo de encaminhá-los o mais antecipadamente possível para o diagnóstico e tratamento precoce com diminuição ou eliminação das sequelas [1][2][3][4] .…”
Section: Introductionunclassified